Amblyopia: neural basis and therapeutic approaches - Bretas,Caio César Peixoto (2016)
ABSTRACT Abnormalities in visual processing caused by visual deprivation or abnormal binocular interaction may induce amblyopia, which is characterized by reduced visual acuity. Occlusion therapy, the conventional treatment, requires special attention as occlusion of the fellow normal eye may reduce its visual acuity and impair binocular vision. Besides recovering visual acuity, some researchers have recommended restoration of stereoacuity and motor fusion and reverse suppression in order to prevent diplopia. Recent studies have documented that the amblyopic visual cortex has a normal complement of cells but reduced spatial resolution and a disordered topographical map. Changes occurring in the late sensitive period selectively impact the parvocellular pathway. Distinct morphophysiologic and psychophysical deficits may demand individualization of therapy, which might provide greater and longer-lasting residual plasticity in some children.